A method for preparing zinc negative electrode material, modified zinc negative electrode and zinc battery

By forming a dense hydrophobic protective layer on the surface of the zinc negative electrode, the problem of short life of the zinc negative electrode during the charge and discharge cycle and the formation of zinc dendrites is solved, and the safety and efficiency of zinc batteries are improved.

CN115241408BActive Publication Date: 2025-02-14STATE GRID SHANGHAI MUNICIPAL ELECTRIC POWER CO +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210945255.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-08
Publication Date
2025-02-14
Estimated Expiration
2042-08-08

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have serious safety hazards. The zinc negative electrode of a water-based zinc ion secondary battery has a short life during the charge and discharge cycle, and is prone to forming zinc dendrites, resulting in short circuits and low Coulomb efficiency.

Method used

A dense hydrophobic protective layer is formed on the surface of the zinc negative electrode. By dispersing fluorinated graphite in a solvent, it is uniformly coated on the zinc negative electrode material to form a strong hydrophobic functional protective layer.

Benefits of technology

Effectively block the corrosion of metal zinc and electrolyte, restrict changes in zinc negative electrodes, reduce the formation of zinc dendrites, extend the life of zinc negative electrodes, and improve the coulombic efficiency of zinc batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115241408B_ABST
    Figure CN115241408B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a zinc negative electrode material, a modified zinc negative electrode and a zinc battery. The method comprises: step 1, dispersing graphite fluoride in a solvent to obtain a dispersion of graphite fluoride, wherein the concentration is 0.01 mg / mL-2 mg / mL, and the concentration can ensure that the graphite fluoride is fully and evenly dispersed. Too much solvent will cause a porous structure to appear during the drying process; step 2, uniformly coating the surface of the zinc negative electrode material with the dispersion of graphite fluoride, and the coating amount is 5 ul / cm 2 ‑50ul / cm 2 , removing the solvent to obtain a modified zinc negative electrode material. The present invention utilizes the interaction between graphite fluoride and the zinc negative electrode to form a dense, highly hydrophobic functional protective layer on the surface of the zinc negative electrode, which can effectively prevent the corrosion of metal zinc with the electrolyte during the electrodeposition process, and effectively constrain the change of the zinc negative electrode, reduce the formation of zinc dendrites, and effectively improve the corrosion and uneven deposition problems of the zinc negative electrode. The preparation method is simple, low-cost, and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a method for preparing a zinc negative electrode material, a modified zinc negative electrode and a zinc battery. Background Art

[0002] In recent years, with the increasing market demand for large-scale energy storage and electric vehicles, the safety of secondary batteries has received widespread attention. For traditional lithium-ion batteries, the organic electrolyte system and highly active metallic lithium used in them lead to serious safety hazards during the use of lithium-ion batteries, limiting their application in the field of large-scale energy storage. Aqueous zinc-ion secondary batteries have attracted widespread attention due to their high safety and low-cost aqueous electrolytes, high-capacity and air-stable zinc negative electrodes. However, due to the high metal activity of metallic zinc, it inevitably reacts with aqueous solution in the electrolyte, causing corrosion and passivation of the zinc negative electrode, resulting in a shorter life of the zinc negative electrode during the charge and discharge cycle. In addition, during the charge and discharge process, the disordered electrodeposition of zinc ions will produce zinc dendrites, resulting in short circuits and low coulombic efficiency of the battery during the cycle.

[0003] The methods reported so far to improve the corrosion and uneven deposition of zinc anodes mainly include: reducing the activity of water with high-salt electrolytes and constructing three-dimensional current collectors, etc. Although these methods can alleviate the above problems to a certain extent, their high costs limit their large-scale promotion. Summary of the invention

[0004] The purpose of the present invention is to improve the corrosion and uneven deposition problems of the zinc negative electrode, modify the zinc negative electrode, and form a dense hydrophobic protective layer on the surface of the zinc negative electrode. The formation method is simple and suitable for industrialization.

[0005] In order to achieve the above object, the present invention provides a method for preparing a modified zinc negative electrode material, which comprises:

[0006] Step 1, dispersing graphite fluoride in a solvent to obtain a dispersion of graphite fluoride at a concentration of 0.01 mg / mL-2 mg / mL, which can ensure that the graphite fluoride is fully and evenly dispersed. Too much solvent will cause a porous structure to appear during the drying process;

[0007] Step 2: Evenly coat the surface of the zinc negative electrode material with the dispersion of graphite fluoride at a coating amount of 5ul / cm 2 -50ul / cm 2 , remove the solvent to obtain a modified zinc negative electrode material.

[0008] Optionally, the solvent is any one of ethanol, DMF, acetonitrile, NMP, methanol, or a mixture of any two or more thereof.

[0009] Optionally, in step 1, ultrasonic dispersion is used, and the ultrasonic treatment time is 4-12 hours to ensure that the graphite fluoride can form a uniform dispersion in the solvent.

[0010] Optionally, in step 2, the coating method includes: any one or any two or more of spin coating, scraper coating, spray coating, and brush coating.

[0011] Optionally, the zinc negative electrode material includes any one or any two or more of zinc foil, zinc alloy, pure zinc powder, and zinc oxide.

[0012] The present invention also provides a modified zinc negative electrode, which comprises:

[0013] Zinc negative electrode body;

[0014] A hydrophobic protective layer is formed on the surface of the zinc negative electrode body, and the hydrophobic protective layer is formed by the above-mentioned preparation method.

[0015] The present invention also provides a zinc battery, which comprises a positive electrode, a zinc negative electrode, and an electrolyte, and is characterized in that the zinc negative electrode is the above-mentioned modified zinc negative electrode.

[0016] Optionally, the positive electrode is selected from any one of a graphite positive electrode, a manganese dioxide positive electrode, a vanadium pentoxide positive electrode, and a Prussian blue positive electrode.

[0017] Beneficial Effects of the Invention

[0018] 1) By utilizing the interaction between graphite fluoride and the zinc negative electrode, a dense and strongly hydrophobic functional protective layer is formed on the surface of the zinc negative electrode. The hydrophobic protective layer can effectively prevent the corrosion of metal zinc with the electrolyte during the electrodeposition process, and effectively constrain the changes of the zinc negative electrode and reduce the formation of zinc dendrites.

[0019] 2) The preparation process of the present invention has the advantages of simple operation, low cost, high efficiency, easy to achieve large-scale and industrial production, and wide application.

[0020] 3) The zinc negative electrode with a hydrophobic protective layer can be used not only in weakly acidic zinc batteries but also in alkaline zinc batteries, and has universal applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope image of the modified zinc negative electrode material prepared in Example 1 of the present invention.

[0022] Figure 2 This is a comparison chart of the hydrophobicity test of the modified zinc negative electrode prepared in Example 1 of the present invention and the untreated zinc sheet.

[0023] Figure 3The graph is a relationship between voltage and time during the charge and discharge cycle of the symmetrical battery prepared in Example 1 of the present invention and the comparative example 1.

[0024] Figure 4 The graph is a relationship between the coulombic efficiency and the cycle number of the asymmetric battery prepared in Example 1 of the present invention and the comparative example 2 during the charge and discharge cycle.

[0025] Figure 5 The graph is a relationship between voltage and time during the charge and discharge cycle of the symmetrical battery prepared in Example 3 of the present invention and the comparative example 3. DETAILED DESCRIPTION

[0026] In traditional lithium-ion batteries, the graphite negative electrode reacts with the electrolyte during the discharge process to form a dense solid electrolyte (SEI) film on its surface. This SEI film can not only inhibit the side reactions between the graphite negative electrode and the electrolyte, but also help stabilize the embedding / extraction of lithium ions in the graphite negative electrode, thereby achieving a stable charge and discharge cycle.

[0027] Based on this, the present invention considers constructing an artificial protective layer on the zinc negative electrode. The present invention finds that the van der Waals force is formed between zinc and graphite fluoride, which is beneficial to obtain a complete protective layer; in addition, the heteroatom fluorine in the graphite has a strong electronegativity, which is beneficial to the nucleation of zinc. The present invention utilizes the interaction between graphite fluoride and the zinc negative electrode to form a dense and strongly hydrophobic functional protective layer on the surface of the zinc negative electrode. The dense hydrophobic protective layer can effectively prevent the corrosion of metallic zinc with the electrolyte during the electrodeposition process, and effectively constrain the changes in the zinc negative electrode and reduce the formation of zinc dendrites. The method specifically includes:

[0028] Step 1, dispersing graphite fluoride in a solvent to obtain a dispersion of graphite fluoride at a concentration of 0.01 mg / mL-2 mg / mL, which can ensure that the graphite fluoride is fully and evenly dispersed. Too much solvent will cause a porous structure to appear during the drying process. The above dispersion can be ultrasonically dispersed, and the ultrasonic treatment time is 4-12 hours to ensure that the graphite fluoride can form a uniform dispersion in the solvent.

[0029] Step 2: Evenly coat the surface of the zinc negative electrode material with the dispersion of graphite fluoride at a coating amount of 5ul / cm 2 -50ul / cm 2 , remove the solvent to obtain a modified zinc negative electrode material.

[0030] The solvent is any one of ethanol, DMF, acetonitrile, NMP and methanol or a mixture of any two or more thereof.

[0031] The coating method includes: any one or any two or more of spin coating, scraper coating, spray coating and brush coating.

[0032] The zinc negative electrode material includes any one or any two or more of zinc foil, zinc alloy, pure zinc powder and zinc oxide.

[0033] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] Commercial graphite fluoride was dispersed in ethanol at a concentration of 0.1 mg / ml. The suspension was treated with ultrasound for 6 hours to obtain an ethanol dispersion of graphite fluoride. The suspension was then evenly coated on zinc foil with a surgical spatula at a coating amount of 10 ul / cm 2 , and then dried in a drying oven at 40°C for 6 hours to evaporate the solvent, thereby obtaining a zinc negative electrode material with a hydrophobic protective layer, as shown in the scanning electron microscope image. Figure 1 As shown in Figure 2, the surface of the Zn negative electrode is completely and evenly covered with a hydrophobic protective layer. Figure 2 As shown, the zinc sheet with graphite fluoride protective layer (Example 1) and the untreated zinc sheet are both dropped with a water drop under the same water content. By comparing the contact angles of the water drop, it can be seen that the protective layer of this example has significantly stronger hydrophobicity.

[0036] The zinc negative electrode material with the hydrophobic protective layer was used as the positive and negative electrodes, and 2 mol / L zinc sulfate was used as the electrolyte to assemble a symmetrical battery, and its electrical performance was tested. Untreated zinc (without the hydrophobic protective layer) was used as the positive and negative electrodes, and 2 mol / L zinc sulfate was used as the electrolyte to assemble a symmetrical battery, as comparative example 1, and its electrical performance was tested. Figure 3 As shown, at 1mA / cm 2 The current density and 1 mAh / cm 2 The untreated zinc (Comparative Example 1) can circulate for 1500 hours at a capacity of , while the untreated zinc (Comparative Example 1) short-circuit occurs after only 300 hours of operation.

[0037] The above-mentioned preparation method was used to coat the graphite fluoride on the titanium foil and use it as the working electrode, zinc as the counter electrode and reference electrode, 2 mol / L zinc sulfate as the electrolyte, and assemble into an asymmetric cell to test its electrical performance. The untreated titanium foil was used as the working electrode, zinc as the counter electrode and reference electrode, 2 mol / L zinc sulfate as the electrolyte, and assembled into an asymmetric cell as comparative example 2 to test its electrical performance. Figure 4 As shown, at 1 mAh / cm 2 Deposition capacity, 1mA / cm 2At a current density of 1.5 Å, the coulombic efficiency (i.e., deposition-stripping efficiency) of zinc in the hydrophobic protective layer of graphite fluoride is as high as 98% (this embodiment), which is much higher than the deposition-stripping efficiency of ordinary zinc sheets (Comparative Example 2) (85% on average). Among them, high deposition-stripping efficiency indicates high reversibility, which also means a longer cycle life for zinc batteries.

[0038] Example 2

[0039] Commercial graphite fluoride was dispersed in DMF at a concentration of 0.2 mg / ml, and the suspension was treated with ultrasound for 10 h to obtain a DMF dispersion of graphite fluoride. The DMF dispersion of graphite fluoride was evenly coated on the zinc foil using a spin coating process (3000 rpm, dripping within 1 minute) at a coating amount of 10 ul / cm 2 , and then dried in a drying oven at 50°C for 6 hours to evaporate the solvent to obtain the target product.

[0040] Example 3

[0041] Commercial graphite fluoride was dispersed in NMP at a concentration of 0.25 mg / ml, and the suspension was treated with ultrasound for 4 hours to obtain a graphite fluoride NMP dispersion. The graphite fluoride NMP dispersion was evenly coated on zinc foil using a brush coating process at a coating amount of 20 ul / cm2, and then dried in a drying oven at 60°C for 12 hours to evaporate the solvent, thereby obtaining the target product.

[0042] The zinc negative electrode with the hydrophobic protective layer was used as the positive and negative electrodes, and 6 mol / L potassium hydroxide was used as the electrolyte to assemble them into a symmetrical battery, and its electrical performance was tested. The untreated zinc (without the hydrophobic protective layer) was used as the positive and negative electrodes, and 6 mol / L potassium hydroxide was used as the electrolyte to assemble them into a symmetrical battery, as Comparative Example 3, and its electrical performance was tested. Figure 5 As shown, at 1mA / cm 2 The current density and 1 mAh / cm 2 The capacity can be cycled for 150 hours (Example 3), which is much higher than that of the ordinary untreated zinc sheet (Comparative Example 3). It can be seen that although the effect of the alkaline zinc battery composed of the zinc negative electrode with a hydrophobic protective layer is slightly worse, it is also significantly higher than the alkaline zinc battery composed of the untreated zinc electrode.

[0043] In some embodiments, a modified zinc negative electrode is provided, comprising: a zinc negative electrode body; and a hydrophobic protective layer formed on the surface of the zinc negative electrode body, wherein the hydrophobic protective layer is formed by the above-mentioned preparation method.

[0044] The zinc negative electrode with a hydrophobic protective layer provided by the present invention can be used not only in weakly acidic zinc batteries (Example 1) but also in alkaline zinc batteries (Example 3), and has universal applicability.

[0045] In some embodiments, a zinc battery is provided, which comprises a graphite positive electrode, a modified zinc negative electrode prepared in the above embodiment 1, and a zinc sulfate electrolyte. The positive electrode can also be selected from any one of a manganese dioxide positive electrode, a vanadium pentoxide positive electrode, and a Prussian blue positive electrode. The electrolyte can also be an alkaline electrolyte, such as a sodium hydroxide electrolyte.

[0046] In summary, the present invention utilizes the interaction between graphite fluoride and the zinc negative electrode to form a dense, highly hydrophobic functional protective layer on the surface of the zinc negative electrode body, thereby achieving surface modification of the zinc negative electrode. The hydrophobic protective layer can effectively prevent the corrosion of metallic zinc with the electrolyte during the electrodeposition process, and effectively constrain the changes in the zinc negative electrode, reducing the formation of zinc dendrites.

[0047] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a modified zinc negative electrode material, characterized in that: The method includes: Step 1, dispersing graphite fluoride in a solvent to obtain a dispersion of graphite fluoride with a concentration of 0.01 mg / mL-2 mg / mL; Step 2: Evenly coat the surface of the zinc negative electrode material with the dispersion of graphite fluoride at a coating amount of 5ul / cm 2 -50ul / cm 2 , removing the solvent, forming a hydrophobic protective layer on the surface of the zinc negative electrode material, and obtaining a modified zinc negative electrode material.

2. The method for preparing the modified zinc negative electrode material according to claim 1, characterized in that: The solvent is any one of ethanol, DMF, acetonitrile, NMP and methanol or a mixture of any two or more thereof.

3. The method for preparing the modified zinc negative electrode material according to claim 1, characterized in that: In step 1, ultrasonic dispersion is adopted, and the ultrasonic treatment time is 4-12h.

4. The method for preparing the modified zinc negative electrode material according to claim 1, characterized in that: In step 2, the coating method includes: any one or any two or more of spin coating, scraper coating, spray coating, and brush coating.

5. The method for preparing the modified zinc negative electrode material according to claim 1, characterized in that: The zinc negative electrode material includes any one or any two or more of zinc foil, zinc alloy, pure zinc powder and zinc oxide.

6. A modified zinc negative electrode, characterized in that It contains: Zinc negative electrode body; A hydrophobic protective layer formed on the surface of the zinc negative electrode body is formed by the preparation method according to any one of claims 1 to 5.

7. A zinc battery comprising a positive electrode, a zinc negative electrode, and an electrolyte, characterized in that: The zinc negative electrode is the modified zinc negative electrode as claimed in claim 6.

8. The zinc battery according to claim 7, characterized in that: The positive electrode is selected from any one of a graphite positive electrode, a manganese dioxide positive electrode, a vanadium pentoxide positive electrode and a Prussian blue positive electrode.

Citation Information

Patent Citations

  • Lithium primary battery and method for producing the same

    CN101877410A

  • Negative electrode for lithium ion secondary battery, and method for producing same

    CN109155401A